Pengaruh Motivasi Kerja dan Lingkungan Kerja terhadap Kepuasan Kerja Karyawan PT. Hijau Pryan Perdana - Nasution, Juhri Abna; Safrida, Safrida; Nasution, Ismail (Universitas Islam Islam Sumatera Utara, 2022)
The problem formulation in this research is whether there is an influence of work motivation and work environment on the job satisfaction of employees PT. Hijau Priyan Perdana. This research aims to find out how work motivation and work environment influence the job satisfaction of employees PT. Hijau Priyan Perdana. The data analysis techniques in this study are descriptive analysis and multiple linear regression analysis. The sample in this research consisted of 35 employees. The analytical technique used is the quantitative method. The results of this research indicate that the Work Motivation variable has a positive and significant effect on Employee Job Satisfaction at PT. Hijau Priyan Perdana. The Work Environment variables have a positive and significant effect on Employee Job Satisfaction at PT. Hijau Priyan Perdana. Work Motivation and Work Environment variables have a positive and significant effect on Employee Job Satisfaction at PT. Hijau Priyan Perdana